EVALUATION OF ENGLISH FOR CHILDREN PROGRAM AT COLORADO COURSE - Dian Eka Gustini; Alexon Alexon; Turdjai Turdjai (DIADIK, 2017)
This research aims to describe the implementation of National Education Standards on the English for Children program based on the Accreditation Standard of Courses and Training from BAN PAUD and PNF. This research was an evaluative research using discrepancy evalution model. Subjects in this study were the eight National Education Standards in the English for Children program at CCPJ. Data were collected by using modified instruments for Course dan Training Accreditation from BAN PAUD and PNF. The methods of data collecting were direct observation method and documentation. Data were analyzed by quantitative descriptive analysis. The results show that the implementation of National Education Standards at CCPJ is in good criteria. Keywords:  implementation of SNP, english for children, course and training program